Politik und Gesellschaft im Vilayet Kosovo und im serbisch beherrschten Kosovo 1870-1914, Bd.5: Berichte der österreichisch-ungarischen Konsuln aus dem zentralen Balkan - Schmitt, Oliver Jens (Verlag der Österreichischen Akademie der Wissenschaften, 2020)
The volumes offer a commented edition of Austro-Hungarian consular reports from the Vilayet Kosovo and for the first years of the Serbian administration in Kosovo, 1870-1914.Volume 1/1: https://e-book.fwf.ac.at/o:1472Volume 1/2: https://e-book.fwf.ac.at/o:1473Volume 1/3: https://e-book.fwf.ac.at/o:1474Volume 1/4: https://e-book.fwf.ac.at/o:1475Volume 1/5: https://e-book.fwf.ac.at/o:1476Maps: https://e-book.fwf.ac.at/o:1477